2015
DOI: 10.5137/1019-5149.jtn.13654-14.1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in patients underwent aneurysmal clipping surgery due to spontaneous subarachnoid hemorrhage

Abstract: ABSTRACTaneurysmal SAHs have been investigated in several studies.The aim of the present retrospective study is to examine the various prognostic factors of the clinical outcomes of 104 patients who underwent a neurosurgical clipping of aneurysms due to aneurysmal SAH between 2008 and 2014. █ mATERIAl and mEThODSThe data of 104 patients that had suffered an aneurysmal SAH were analyzed. The patients were recruited between 2008 and 2014 at the Neurosurgery Clinic of Haydarpasa Numune Training and Research Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…The only significant prognostic factor was in patients with Fisher grade II, and all patients had favorable outcome. This is in agreement with other previously published studies investigating the prognostic factors after microsurgical clipping of cerebral aneurysms [15,17]. A study by Dilvesi et al showed that the Fisher Grade is not significant in predicting the intensity of cerebral vasospasm in patients hospitalized with intracranial aneurysm rupture [21].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The only significant prognostic factor was in patients with Fisher grade II, and all patients had favorable outcome. This is in agreement with other previously published studies investigating the prognostic factors after microsurgical clipping of cerebral aneurysms [15,17]. A study by Dilvesi et al showed that the Fisher Grade is not significant in predicting the intensity of cerebral vasospasm in patients hospitalized with intracranial aneurysm rupture [21].…”
Section: Discussionsupporting
confidence: 92%
“…The authors do not recommend postponing treatment in patients between days 5 and 10 after subarachnoid hemorrhage [4]. Orakdogen and others evaluated the timing of surgery with several prognostic factors in patients who underwent microsurgical clipping for ruptured cerebral aneurysms and demonstrated that the rate of mortality was significantly higher in the day 0 period and the rate of mortality did not differ significantly from the other stages of the disease [17]. The aforementioned studies supported the practice of aneurysm treatment once diagnosed even in the period of vasospasm as in our protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was also found that the risk of IPR-associated periprocedural death/disability was 31% with surgical treatment and 63% with endovascular in 2008. [ 4 ] In addition, the mortality of intracranial aneurysm decreased to <14% with neurosurgical treatment [ 5 ] and <1% with endovascular treatment [ 6 ] in 2016. Strengthening the standardized training for residents can effectively reduce medical disputes, self-protect medical staff, and improve medical-patient communication.…”
Section: Introductionmentioning
confidence: 99%
“…The other factors were mainly in line with the detected risk factors for an impaired outcome after aSAH in previous studies. 10,19,22,25,28,34 Aneurysm size was not an independent risk factor for a poor outcome in PCoA aneurysm patients, even though it might be for aneurysms at another location. 22,28 Large or giant PCoA aneurysms were rare, which might affect this result.…”
Section: Resultsmentioning
confidence: 91%